Association of the type of counselor with suicidal ideation and suicide attempts: a survey of South Korean adolescents - Yunkyung Kim (BMC, 2021)
Abstract Background Counseling for adolescents who consider or attempt suicide may help reduce suicide rates. However, the impact of the type of counselor (e.g., father, mother, sibling, friend, teacher, other) on suicidal ideation/suicide attempts remains unclear. Therefore, we examined this association in Korean adolescents. Methods Using data from the 2015 Korea Youth Risk Behavior Web-based Survey of 65,485 adolescents, we examined risk factors for suicidal ideation/suicide attempts according to sex using a multiple logistic regression analysis. In a subgroup analysis, we investigated the associations between counselor type and suicidal ideation/suicide attempts stratified by the cause of stress for both sexes. Results Male participants were less likely to consider suicide when counseled by their mother (odds ratio [OR] 0.80; 95% confidence interval [CI] 0.70–0.90) or friend (OR 0.89; 95% CI 0.80–0.99) and to attempt suicide when counseled by a friend (OR 0.74; 95% CI 0.60–0.92) than were those who did not receive any counseling. Female participants were less likely to attempt suicide when counseled by their mother (OR 0.66; 95% CI 0.53–0.82) or friends (OR 0.70; 95% CI 0.58–0.83) than when not counseled. Furthermore, adolescents with achievement/career choice-related and family problems were at a lower risk of suicide ideation/suicide attempts when counseled by their mother or friend than when they received no counseling. Conclusions Suicidal ideation/suicide attempts showed different associations for both sexes in accordance with the type of counselor. Even if counseling by specialists for issues such as achievement/career choice-related or family matters is needed, the risk of suicide could be reduced through counseling by the people around them. Therefore, adolescents should form mutually supportive relationships through active communication with surrounding people.